Customers’ Perceptions on the Objectives, Characteristics and Selection Criteria of Islamic Bank in Thailand - Nasrina Lateh; Suhaiza Ismail; Noraini Mohd Ariffin (Gadjah Mada International Journal of Business, 2009)
Due to relatively new establishment of islamic bank in Thailand and paucity of empirical research undertaken in the area, this study intends to capture the perceptions of Thai customers towards the objectives and characteristics of the islamic bank. In addition, this study aims to determine the important bank selection criteria as perceived by the customers and the differences in the perceptions of moslem and non-moslem customers were identified. The study surveys a sample of 462 respondents. The empirical findings show that the Thai customers know that the essential characteristic of the islamic bank is interest prohibition. They tend to support the idea that the islamic bank should strive to achieve its social objectives more than the commercial objectives. In addition, the results showed that there are differences between the Thai moslem and non-moslem customers’ preferences toward various bank selection criteria. The moslems highly considered the interest-free saving facilities, while the non-moslems tended to concern more about its reputation and image, and knowledgeable and competent personnel.